Transformation of islamic religious education learning through religious literacy assessment instruments - Rachmaningtyas, Nur Anisyah; Prihono, Eko Wahyunanto; Naqsyahbandi, Fajar (Al-Misbah (Jurnal Islamic Studies), 2025)
This study aims to assess the quality of the religious literacy assessment instrument and describe the religious literacy of elementary school students in IRE. This type of research is quantitative research with an instrument development approach using the Mardapi development model. The instrument is in the form of 25 multilevel multiple-choice questions, validated by three experts, and piloted on 233 students from nine elementary schools in the Special Region of Yogyakarta selected through a stratified random sampling technique. These schools represent high, medium, and low categories, so the results reflect the diversity of student ability levels. The analysis shows that the instrument is categorized as suitable for use, with high validity (0.85) and high reliability (0.80). The instrument is also assessed to meet scientific standards through Confirmatory Factor Analysis (CFA), so it is able to measure religious literacy objectively and comprehensively. The measurement results show that the level of religious literacy of students is still low, namely 33.00%. This finding provides important insights for IRE teachers to develop more meaningful and transformative learning evaluations. In addition, the instruments developed can be a reference for other schools in developing comprehensive evaluations, while also building a religious, tolerant, and critical generation in facing the challenges of the times.